2008
DOI: 10.1097/01.smj.0000308363.10237.54
|View full text |Cite
|
Sign up to set email alerts
|

Use of Conventional and Nonconventional Treatments for Osteoarthritis in the Family Medicine Setting

Abstract: Providers should make sure to ask patients about all treatments they are using for their osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 26 publications
6
21
2
Order By: Relevance
“…Our work extends similar reports based on the general US population [29,30], as well as persons with self-reported arthritis [13], to a population with radiographically confirmed knee OA. Our work is not consistent with other reports [14,17], however. Comparing results of CAM use across studies is challenging because researchers often use different definitions of CAM.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our work extends similar reports based on the general US population [29,30], as well as persons with self-reported arthritis [13], to a population with radiographically confirmed knee OA. Our work is not consistent with other reports [14,17], however. Comparing results of CAM use across studies is challenging because researchers often use different definitions of CAM.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with other studies [13], we found that CA used more biologically based supplements, especially glucosamine and chondroitin, and chiropractic services relative to AA. Also consistent with the literature [14,16,17], we found that AA used more spiritual and religious activities and topical agents relative to CA.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…8 Currently, there are no curative therapies for OA and clinical guidelines recommend both pharmacological and non-pharmacological methods to relieve symptoms. 9,10 CAM use is common among OA patients 11,12 perhaps due to ineffective pain management or adverse effects associated with conventional medicine 13,14 or because of the patients’ own health beliefs. 15 …”
Section: Introductionmentioning
confidence: 99%